Answers

2014-08-04T17:34:22+08:00
*using binomial theorem: [(x + y)^2 - (x - y)^2] = 4xy; [(x^2 + 2xy +y^2) - (x^2 - 2xy +y^2)] = 4; *eliminating x^2 and y^2: [2xy - (-2xy)] = 4xy; 4xy = 4xy
1 5 1
2014-08-04T17:48:25+08:00
[(x+y)+(x-y)][(x+y)-(x-y)] = 4xy
[x+y+x-y][x+y-x+y]       === negative times positive x equals negative x and negative y times negative equals positive y , don't mind the 4xy on the opposite side!
[x+x+y-y][x-x+y+y] =4xy
[2 x][2 y] = 4xy
2x · 2y = 4xy
2 · xy = 4xy
4xy = 4xy
  √   =  √ They are equal, so this equation and the answer is equal to 4xy.

1 5 1